ANALISIS PELAKSANAAN PROGRAM JAMINAN KESEHATAN NASIONAL DI DINAS KESEHATAN KABUPATEN ROKAN HILIR - Norjani Norjani (Universitas Pahlawan, 2022)
The National Health Insurance is part of the National Social Security System organized by the Health Social Security Administration (BPJS) through a mandatory social health insurance mechanism. The Social Security Administering Body. is a legal entity established to administer social security programs. Participants of the Health Social Security Administering Body are divided into 2 groups based on the origin of the funding. The first group is Contribution Recipients, participants in the category of those with economic difficulties. The second group of BPJS Health participants are those who belong to the Non-PBI (Contribution Recipients) group. The Health Service is an office that facilitates health and provides technical implementers of public health services that provide non-specialist individual health services for observation, diagnosis, treatment, treatment and or other health services. The formulation of the problem in this study is why the management of the National Health Insurance budget by the Health Social Security Administration at Balai Jaya Health Center, Rokan Hilir Regency has not been maximized. planning for the National Health Insurance in the working area of ​​the Rokan Hilir Health Service. This research method uses a qualitative approach with a descriptive type of research. The results of this study indicate that the planning of the National Health Insurance at the Health Office of Rokan Hilir Regency has not been implemented properly. This is based on the fact that there are still many people who have not been integrated into the National Health Insurance . Based on the Minister of Social Affairs Regulation Number 170 of 2015 the quota for JKN PBI Rokan Hilir participants is 184,419 people, but for JKN PBI Rokan Hilir participants it is only 1,762 people. Keywords : Planning, National Health Insurance